(untitled) (Medical Forum Monthly, 2024)
Objective: To assess the clinical efficacy of mannitol infusion in chronic liver disease patients presenting with hepatic encephalopathy. Study Design: A randomized control trial study Place and Duration of Study: This study was conducted at the Department of medicine Shalamar hospital, Lahore from January 2022 to January 2023. Methods: In this randomized control trial 95 patients were selected from the male and female medical wards of Shalamar Hospital. A random assignment was made to place each patient in one of the two groups. Group B followed a regular treatment plan, whereas Group A added mannitol to their usual regimen. Following that, patients underwent daily evaluations, and the number of days they spent in the hospital as well as any improvements in their symptoms and overall health were noted. Serum electrolytes in groups A and B were also tested on days 1 and 3. SPSS 17 was used to arrange and analyze the data. Results: Results indicated that 40 patients (88.9%) improved and were discharged, whereas 5 patients (11.1%) passed away while receiving therapy in group A. In comparison, among group B, 45 patients (90%) made improvements; nevertheless, 5 patients (10%) passed away during treatment. Mean Na+ concentration in Group A on day 1 of treatment was 137.31mmol/L and on day 3 it was 135.42mmol/L whereas mean K+ concentration in group A on day 1 was 4.0mmol/L and on day 3 it was 3.8.mmol/L. Mean Na+ concentration in Group B on day 1 of treatment was 137.6mmol/L and on day 3 it was 136.0mmol/L whereas mean K+ concentration in group B on day 1 was 4.1mmol/L and on day 3 it was 3.9mmol/L. Conclusion: Our research revealed that although the use of Mannitol did not result in any changes to the overall course of the disease, it did improve the quality of life for patients and reduced the stay in hospital.